“Características botánicas y agronomicas de híbridos de tabaco negro de capa bajo condiciones de riego en Juan Guerra San-Martín” - Gatica.Acosta, Erika Raquel (2002)
With the objective of evaluating the hybrid botanical and agronomic characteristics of 4 of black tobacco far layer, under watering conditions, it was carried out the present work in lands of property of the Company Tobaccos of the Peru S.A, located approximately to 11.5 Km. of Tarapoto, to 232 m.s.n.m., South latitude 06º 35' and Longitude West 76º 19 in Juan Guerra district, county and department of San Martin. The experiment was driven under the Complete Design Randomizado with tour treatment and tour repetitions. The hybrid $9107 x 89105 with 99.7% of germinated seeds, 92.2% of vigor, 96.60% emerged seedling, 84. 85% plants· capable to the transplant, in field 100 seizure%. The fciur hybrid reached their fenology period in 131 days with curved of similar growth and the height varied from 250 to 265.63 cm. The buttoned, beginning and 50 flowering% showed precocity the hybrid one 98142x98152 and the latest S9106XS9105 Considering. With regard to the size of the leaves in the first ene, third and sixth crop, alone in the first one the hybrid S8102xS8107, S9107XS9105 and 98142x98152 with 43.08, 41.68 and 41.38 cm stood out in longitude; the hybrid S8102xS8107 with 29.28, 33.38 and 27.1 O cm reached bigger leaf width; the hybrid ene 98142x98152 with 35.67, 34.54 and 32.85 degrees had bigger insert angle. The hybrid S9107XS9105 and 89106XS9105 with 27 and 28 leaves fer plant registered t;>igger nümber of leaves. The petals varied from pink color to rosy vermilion with peduncles and green sepals The S9106XS9105 with 16 779.40 it registered the biggest yield in fresh leaf. The hybrid ali ones showed certain susceptibility to Fusarium solani, Cercospora nicotianae and it would A/ternaria alternata